Larger antelopes are sensitive to heat stress throughout all seasons but smaller antelopes only during summer in an African semi-arid environment - Shrestha, A. K.; van Wieren, S. E.; van Langevelde, F.; Fuller, A.; Hetem, R. S.; Meyer, L.; de Bie, S.; Prins, H. H. T. (International journal of biometeorology, 2014)
Heat stress can limit the activity time budget of ungulates due to hyperthermia, which is relevant for African antelopes in ecosystems where temperature routinely increases above 40 °C. Body size influences this thermal sensitivity as large bodied ungulates have a lower surface area to volume ratio than smaller ungulates, and therefore a reduced heat dissipation capacity. We tested whether the activity pattern during the day of three antelope species of different body size—eland, blue wildebeest and impala—is negatively correlated with the pattern of black globe temperature (BGT) during the day of the ten hottest days and each season in a South African semi-arid ecosystem. Furthermore, we tested whether the larger bodied eland and wildebeest are less active than the smaller impala during the hottest days and seasons. Our results show that indeed BGT was negatively correlated with the diurnal activity of eland, wildebeest and impala, particularly during summer. During spring, only the activity of the larger bodied eland and wildebeest was negatively influenced by BGT, but not for the smallest of the three species, the impala. We argue that spring, with its high heat stress, coupled with poor forage and water availability, could be critical for survival of these large African antelopes. Our study contributes to understanding how endothermic animals can cope with extreme climatic conditions, which are expected to occur more frequently due to climate change.